Juridical Analysis of the Crime of Child Abuse Is Also Done by Children - Abdul Hamid (The International Journal of Law Review and State Administration, 2023)
The purpose of this study is to determine the qualifications of criminal acts of sexual abuse of children in the view of criminal law. And to find out the application of criminal law to the crime of child abuse committed by children in Decision Number 8/Pid.Sus-Anak/2017/PN.Tgn. The research method uses normative law which places law as a system of norms, concerning principles, rules, laws and regulations, court decisions, agreements, and doctrines. Primary, secondary, and tertiary research methods are data obtained from the literature that have a relationship with the research focus. In normative legal research, the main source of data from primary law includes regulations, legislation, and legal materials. secondary includes legal books, legal experts, and scholarly academics. Tertiary includes an explanation of primary legal materials and secondary legal materials. Conclusion Qualification of criminal acts of sexual abuse of children in the view of criminal law can be qualified in Articles 290-296 of the Criminal Code as lex generalis and Articles 76E and Article 82 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2014 concerning Child Protection as lex specialis. The application of material criminal law by the Panel of Judges of the Tangerang District Court in case Number 8/Pid.SusAnak/ 2017/PN.Tgn which stated that the defendant MF had been legally and convincingly proven guilty of committing the crime of sexual abuse of a child with the victim NPA regulated in Article 82 Jo. Article 76E UU RI No. 35 of 2014 concerning Amendments to RI Law No. 23 of 2002 concerning Child Protection is correct.